(untitled) - Ireno J Manguiat (Los Bamos, Languna, Philippines, 1998)
The book discusses the utilization of sewage sludge which is an environmental pollutants as an organic fertilizer for upland rice and pechay. It also addresses the issuesof heavy metal accumulation and pathogenic contamination of sewage sludge - teated soils
Keywords: agriculture - economic aspects